(3TQM GdThGgO GdUZQis - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj GdMfaj,J (B855 (3g` s
(3ChdgG (B:s
(3hHYO, jbhd(B: (3Ef LdI ef GdCPcjGA hNdI ef GdCdHGA hNGWHhG HCf TQM GdThGgO GdPj febJg s
(3BNQgG (B:s
(3hGdhghH eHGdZI hGgH, hGdeLRd ef CLRd EPG CYWi YWGA cKjQkG bGd GdeDda QMeg Gddg(B: (3hgPG BNQ eG GNJUQfGg ef GdThGgO s
(3fSNI KGfjI JJab aj ChdgG eY GdfSNI GdChdis
(3HGNJdGa aj HYV GdCdaGX ceG jJab BNQgG eY BNQgGs
(3HBNQgG Jedc SfI (B849(3g`s
(3HgG fXGe GdJYbjHIs
(3hHChdgG TQM OjjGLI GdcJGH ddeDda faSgs
(3jdjg agQS ddCHhGHs
Keywords: (3GdfMhs